(Keynote) Nanoscale Memories: What Does Physics Have to Say?. (9th September 2015) - Zhirnov, Victor V.; Meade, R; Pandey, S. C.; Sandhu, G
Abstract : The central question addressed in this paper is: What is the smallest volume of matter needed for memory devices? It will be shown that, at least in principle, 1-nm devices can be envisioned, which are based on the re-arrangement of atoms; examples include atomic/ionic switches and resistive memory (ReRAM). While theoretical feasibility of the 1-nm devices has been justified based on electrical properties of the few-atom systems, it is still an open question whether such small structure could have sufficient thermal stability for reliable operation. For example, Joule heat will be released as the current passes through the structure, which can potentially destroy the few-atom conductive bridge (CB). In this paper, initial studies of thermal properties of atomic contacts and nanoscale interfaces are presented.